The Role of Chloroplast DNA Markers (psbA) in Maintaining the Position of Lemnoideae - Sururi, Zaki Fahreza; Nururrahmani, Azmah; Sihombing, Maria Engzelita; Hidayat, Topik (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
The duckweed plant group belongs to the botanical family Araceae and has the potential as a food source. It is difficult to classify and the plants were originally grouped as the Lemnaceae family. However, current molecular taxonomy studies revealed the integration of Lemnaceae into the Araceae family, thus becoming the Lemnoideae subfamily. It is necessary to strengthen the position of Lemnoideae in Araceae using molecular marker psbA from chloroplast DNA This study aimed to determine the role of the psbA chloroplast DNA marker in regulating the position of Lemnoideae. A total of 41 sequences of the psbA gene taken from the species from seven subfamilies in Araceae and one outgroup were collected from the NCBI GenBank and then arranged in FASTA format. Sequence data was then aligned by ClustalX, and phylogenetic trees were reconstructed using PAUP and MEGA. From the resulting phylogenetic trees, it can be conferred that the Lemnoideae subfamily does not form a monophyletic group. Thereby, this in silico study using psbA markers concludes the position ofthe Lemnoideae subfamily in the family Araceae and we recommend not separating the plant group from the family Araceae.